A Tree Soft Set Framework for Evaluating Teaching Quality in University Physics Programs: Enhancing Precision and Decision-Making - Hongzhi Zhao; Fengqiang Zhang (Neutrosophic Sets and Systems)
Education in physics is at a crossroads. Numerous nations have middling or worse levels of scientific literacy, according to international research, and their students are viewed as being ill-equipped to handle the challenges going forward. The governmental level has acknowledged the necessity of high-quality development. The article focuses on evaluating physics education is taught and learned through experiments and real-world experiences. We propose a multi-criteria decision making (MCDM) approach to deal with various factors in evaluation of teaching quality in physics programs. We integrate the MCDM method with the Tree Soft Set (TSS) to show the relationship between the different nodes. The root node is the main objective in this study, the first level the main factors, and the second level is the sub factors. The MCDM is used with the single valued neutrosophic sets (SVNSs) to deal with vague data. We gathered five main factors and 15 sub factors in this equation. We compute the factors weights using the AHP method to build the pairwise comparison matrix to evaluate them.